Exploring the relationships between composite scores of disease severity, seizure-freedom and quality of life in Dravet syndrome. - Strzelczyk, Adam; Kurlemann, Gerhard; Bast, Thomas; Bettendorf, Ulrich; Kluger, Gerhard; Mayer, Thomas; Neubauer, Bernd A.; Polster, Tilman; von Spiczak, Sarah; Trollmann, Regina; Wolff, Markus; Toward, Toby; et al. (Neurological Research and Practice, 2022)
BACKGROUND: In Dravet syndrome (DS), a rare epileptic and developmental encephalopathy, the effectiveness of a new treatment is predominantly measured in terms of seizure frequency. However, this may not fully capture the impact of a treatment on the broader aspects of the syndrome and patients' health-related quality of life (HRQoL). Using a previously published survey which collected data from DS patients and their carers on the broader manifestations of their syndrome, their HRQoL, and their experience of seizures, this study created composite measures of symptom severity to offer new perspectives on the multifaceted aspects of this rare condition. METHODS: Survey responses on the severity of physical and psychosocial symptoms were combined with independent assessments of disability and care need, to generate three composite symptom scores assessing the manifestations of DS (physical, psychosocial and care requirements). Variation in HRQoL was investigated in multiple regression analyses to assess the strength of association between each of these composite measures and three forms of seizure measures (seizure frequency, days with no seizures and longest interval without seizures), as experienced over a 4- and 12-week period. RESULTS: Composite scores were calculated for a cohort of 75 primarily paediatric patients who were enrolled in the study. Strong associations were found between each of the three composite symptom scores and each of the three seizure measures, with the regression coefficient on symptom score highly significant (p ≤ 0.001) in all nine comparisons. Separate regressions using predictors of HRQoL (Kiddy KINDL and Kid KINDL) as the dependent variable were inconclusive, identifying only behavioural/attention problems and status epilepticus as significant predictors of HRQoL. CONCLUSIONS: These results allow the development of a composite score that may be useful in developing a clinical understanding of the severity of DS for an individual patient and establishing their treatment goals. Where measurement of long-term sequalae of disease is not feasible, such as clinical trials, correlation of the composite score with experience of seizures and seizure-free periods may allow a better contextualisation of the results of short-term assessments. TRIAL REGISTRATION: German Clinical Trials Register (DRKS), DRKS00011894. Registered 16 March 2017, http://www.drks.de/ DRKS00011894.
EVALuna2:516469